2011
DOI: 10.4049/jimmunol.1001455
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 Phosphorylation Mediates Resistance of Primary Human T Cells to Regulatory T Cell Suppression

Abstract: Human autoimmune diseases are characterized by systemic T cell dysfunction, resulting in chronically activated Th1 and Th17 cells that are inadequately suppressed by regulatory T cells (Tregs). IL-6, which is overexpressed in tissue and serum of patients with autoimmune diseases, inhibits human Treg function. We sought to determine the mechanism for the antitolerogenic properties of IL-6 by examining the signaling pathways downstream of IL-6R in primary human T cells. Inhibition of Stat3 signaling in MLCs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 45 publications
11
85
1
2
Order By: Relevance
“…Specifically, Goodman and colleagues demonstrated that inhibition of STAT-3 restores immunosuppressive function by T regs stimulated previously with IL-6 [47]. Our results are consistent with this notion, and imply that increased STAT-3 phosphorylation in T regs is the hallmark of resistance to suppression in SLE.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Specifically, Goodman and colleagues demonstrated that inhibition of STAT-3 restores immunosuppressive function by T regs stimulated previously with IL-6 [47]. Our results are consistent with this notion, and imply that increased STAT-3 phosphorylation in T regs is the hallmark of resistance to suppression in SLE.…”
Section: Discussionsupporting
confidence: 81%
“…However, the role of ubiquitination in resistance to suppression phenotype in SLE has not been defined completely. Although many studies have suggested that resistance to suppression in SLE is due to an effector T cell resistance and not to an abnormal regulatory function [15,16], it has been demonstrated that this subpopulation displays some molecular defects which could be associated with the acquisition of an effector phenotype [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can offer two possible explanations: first, Ag dose has been shown to be an important determinant for Treg differentiation in which high Ag doses favor the induction of effector T cells, whereas low Ag doses lead to increased Treg differentiation (43). Second, it has been shown that the inflammatory environment, in particular the levels of the proinflammatory cytokine IL-6, critically influence the balance of Treg versus T effector differentiation (44,45). Interestingly, DC-T cell interaction in the presence of high Ag doses favors the production of IL-6 and hence the suppression of Treg induction (43).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to Treg-mediated suppression has previously been associated with activation of STAT3 in responder T cells (48). We therefore measured STAT3 phosphorylation in CD161 + and CD161…”
Section: Cd161mentioning
confidence: 99%